PENGARUH UPAH DAN INSENTIF KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT. MILANO PANAI TENGAH - Efendi, Ruslan; Lubis, Junita; Elvina, Elvina (Fakultas Ekonomi dan Bisnis (FEB) Universitas Labuhanbatu, 2020)
ABSTRACKThis study aims to determine how the influence of wages and incentives on performance at PT Perkebunan Milano. This study uses data collection methods by distributing questionnaires. The population and sample used in this study were 57 employees of PT Perkebunan Milano. Hypothesis testing in this study uses a validity test analysis tool, reliability test, the classic assumption test of multiple linear regression, (t test), (F test), and the coefficient of determination (R2). The results of this study indicate that there is a positive influence The results of this study indicate that partially (t test) wages and a positive and significant effect on employee performance. with a t count of 2,422. Incentives have a positive and significant effect on performance with t count of 6.114. Simultaneously wages and incentives together have a positive and significant effect on performance, with an F count of 22,458. Through testing the coefficient of determination (R Square) of 0.454 or 45.4% which shows that the performance is explained by wages and the remaining incentives of 54.6% are explained by other variables not included in this study.Â Keywords: Wages, Incentives, Employee PerformanceÂ